Challenges of e-GP implementation in public procurement: case study on Election Commission Secretariat, (a constitutional organization) Dhaka, Bangladesh - Mollik, Md. Ruhul Amin (Brac University, 2024)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.